An inability to learn to read caused by shaken baby syndrome. (28th April 2014) - Bevilacqua, Leonardo; Kuczynski, Adam; James-Galton, Merle; Leff, Alex P
Abstract : We report a 12-year-old boy who suffered from shaken baby syndrome at the age of 4 months and has been unable to learn to read even high-frequency, three-letter words, despite slow but accurate letter naming. He had a right homonymous hemianopia and evidence of impaired higher visual function, but not at a severe enough level to account for his inability to read. Speech production and reception of language were impaired for his age but at least of an order of magnitude better than his reading performance. MRI scanning revealed focal damage to the dorsal and ventral reading pathways. This case challenges the Kennard principle, a widely accepted assumption which claims that the earlier a brain injury occurs, the better the recovery. It also adds to the growing literature suggesting that early damage to multiple parts of the language learning network can result in relatively selective impairments later in life.